Craniofacial Microsomia: Goldenhar Syndrome in Association with Bilateral Congenital Cataract - U. D. Shrestha; S. Adhikari (Case Reports in Ophthalmological Medicine)
Craniofacial microsomia (CFM) includes a spectrum of malformations primarily involving structures derived from the first and second branchial arches. Patients with hemifacial microsomia and epibulbar dermoids are said to have Goldenhar syndrome (GHS). Four-month-old boy with whitish pupillary reflex presented with the features of GHS in pediatric ophthalmology clinic. The child had ocular and auricular manifestations. There were no vertebral anomalies, but he had bilateral congenital cataract. The peculiarity of this case is the presence of the bilateral total congenital cataract, in association with CFM. There is absence of epibulbar dermoid or lipodermoid in the eyes, although the child had features of GHS. In addition to it, anesthetic intubation was smooth in this case. Any case diagnosed with CFM and/or GHS needs treatment through multidisciplinary approach, consultation in ophthalmology department is one of them.